Clinical Outcomes and Prognosis Factors of Nivolumab Plus Chemotherapy or Multitarget Tyrosine Kinase Inhibitor in Multi-Line Therapy for Recurrent Hepatitis B Virus-Related Hepatocellular Carcinoma: A Retrospective Analysis - Chen, Chao; An, Li; Cheng, Ying; Luo, Xianwen; Li, Zixiong; Liu, Xiufeng (Frontiers in Oncology, 2020)
Background: To investigate the potential predictors of nivolumab plus chemotherapy or multitarget tyrosine kinase inhibitor (TKI) treatment response in patients with recurrent hepatitis B virus-related hepatocellular carcinoma (HCC). Methods: We retrospectively evaluated patients with recurrent hepatitis B virus-related HCC who underwent nivolumab plus chemotherapy or TKI treatment between July 2017 and June 2019 at Jinling Hospital in China were included in this study; these patients also had both complete medical charts and follow-up data available. Overall survival (OS) and progression-free survival (PFS) were calculated from the date of nivolumab initiation. Survival data were compared using log-rank tests, and the associations of patient characteristics with survival were estimated using Cox regression models. Results: A total of 22 HCC patients were included in this cohort and constituted the basis for this analysis. We identified 20 progressed cases (91%) and 16 deaths (73%) at a median follow-up of 8.8 months (range 1-25). The median OS from the time of nivolumab initiation was 10.7 months (95% CI, 0.8-20.6 months), with a median PFS of 5.1 months (95% CI, 3.1-7.0 months). We divided the patients into 2 risk groups according to a nomogram built by age, ECOG status, hepatectomy status and TACE use. The median PFS was 8.2 ± 2.8 months in the low-risk group compared with 1.9 ± 0.4 months in the high-risk group (p = 0.0018). The median OS was estimated as 16.8 ± 4.9 months for low-risk patients versus 8.6 ± 3.5 months for high-risk patients (p = 0.13). Conclusion: Nivolumab combined with chemotherapy or TKI treatment is effective in patients with recurrent hepatitis B virus-related HCC; it is suggested that previous TACE treatment is associated with a better PFS, and worse PFS in those received hepatectomy in the patients. Prospective studies are warranted to evaluate the effects of nivolumab combine chemotherapy or TKI on recurrent hepatitis B virus-related HCC.